1990
DOI: 10.1056/nejm199007263230404
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Risk of Thrombocytopenia in the Offspring of Pregnant Women with Presumed Immune Thrombocytopenic Purpura

Abstract: The absence of a history of immune thrombocytopenic purpura or the presence of negative results on circulating-antibody testing in pregnant women indicates a minimal risk of severe neonatal thrombocytopenia in their offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(32 citation statements)
references
References 22 publications
0
28
0
4
Order By: Relevance
“…19,20 The individual risk for intraoperative fatal bleeding in the fetus cannot be precisely determined.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The individual risk for intraoperative fatal bleeding in the fetus cannot be precisely determined.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that severe thrombocytopenia, a history of splenectomy and high platelet antibody titers in the mother may be indicative of neonatal thrombocytopenia [7]. Samuel et al [8] reported that 40% of infants born to mothers with a previous diagnosis of ITP were thrombocytopenic at birth; bleeding complications were seen in 6% of those cases. Thrombocytopenia was seen slightly more than expected in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Durch den Transfer von Autoantikörpern der Mutter mit ITP über die Plazenta kann es zu einer Thrombozytopenie bei Feten und Neugeborenen kommen, wobei grundsätzlich auch das (seltene) Risiko einer zerebralen Blutung besteht. In einer Serie von Studien zur ITP bei Schwangeren [42][43][44][45][46][47] kamen nur 13,6 % der Neugeborenen mit einer Thrombozytenzahl unter 50 × 10 9 /l zur Welt, bei 1,3 % war es zu einer zerebralen Blutung gekommen. Nach einer Zusammenstellung von Gernsheimer soll die Wahrscheinlichkeit einer Thrombozytopenie beim Neugeborenen bei 5 -25% liegen [48].…”
Section: Immunthrombozytopenie Während Der Schwangerschaftunclassified